Omnivores Going Astray: A Review and New Synthesis of Abnormal Behavior in Pigs and Laying Hens - Brunberg, Emma I.; Rodenburg, T. Bas; Rydhmer, Lotta; Kjaer, Joergen B.; Jensen, Per; Keeling, Linda J. (Frontiers in Veterinary Science, 2016)
Pigs and poultry are by far the most omnivorous of the domesticated farm animals and it is in their nature to be highly explorative. In the barren production environments, this motivation to explore can be expressed as abnormal oral manipulation directed towards pen-mates. Tail biting in pigs and feather pecking in laying hens are examples of unwanted behaviors that are detrimental to the welfare of the animals. The aim of this review is to draw these two seemingly similar abnormalities together in a common framework, in order to seek underlying mechanisms and principles. Both tail biting and feather pecking are affected by the physical and social environment, but not all individuals in a group express these behaviors and individual genetic and neurobiological characteristics play an important role. By synthesizing what is known about environmental and individual influences, we suggest a novel possible mechanism, common for pigs and poultry, involving the brain-gut-microbiota axis.